TP3, an antimicrobial peptide, inhibits infiltration and motility of glioblastoma cells via modulating the tumor microenvironment - Ying‐Fa Chen; Po‐Chang Shih; Hsiao‐Mei Kuo; San‐Nan Yang; Yen‐You Lin; Wu‐Fu Chen; Shiow‐Jyu Tzou; Hsin‐Tzu Liu; Nan‐Fu Chen (Cancer Medicine, 2020)
Abstract Glioblastoma multiforme (GBM) is a cancer of the central nervous system with limited therapeutic outcomes. Infiltrating cancer cells are the contributing factor to high GBM malignancy. The intracranial brain cancer cell infiltration is a complex cascade involving adhesion, migration, and invasion. An arsenal of natural products has been under exploration to overcome GBM malignancy. This study applied the antimicrobial peptide tilapia piscidin 3 (TP3) to GBM8401, U87MG, and T98G cells. The cellular assays and microscopic observations showed that TP3 significantly attenuated cell adhesion, migration, and invasion. A live‐cell video clip showed the inhibition of filopodia protrusions and cell attachment. Probing at the molecular levels showed that the proteolytic activities (from secretion), the mRNA and protein expression levels of matrix metalloproteinases‐2 and ‐9 were attenuated. This result strongly evidenced that both invasion and metastasis were inhibited, although metastatic GBM is rare. Furthermore, the protein expression levels of cell‐mobilization regulators focal adhesion kinase and paxillin were decreased. Similar effects were observed in small GTPase (RAS), phosphorylated protein kinase B (AKT) and MAP kinases such as extracellular signal‐regulated kinases (ERK), JNK, and p38. Overall, TP3 showed promising activities to prevent cell infiltration and metastasis through modulating the tumor microenvironment balance, suggesting that TP3 merits further development for use in GBM treatments.